Symbology of Animal Motifs in the Verneh Textures of Shahsevan Tribe - Sanam Arzani; Reza Rezalou (Anastasis: Research in Medieval Culture and Art)
Most of the nomads of East Azerbaijan province belong to the tribes of Arasbaran and Shahsevan, nine independent tribes in the Yaylak period, and seven independent tribes in the Qishlaq period. Shahsevan nomads are composed of different tribes, such as Ajirlu, Moghanlu, Giglu, Qaralar Meshgini etc. Verneh, as a type of carpet, Maffrash or means of carrying household furniture, were mainly woven by nomads and some villagers in the settlement of Shahsevan nomads in Azerbaijan and some surrounding areas, such as Pars Abad, Germi and Meshgin Shahr counties of Ardabil province, and Ahar and Kaleybar counties of East Azerbaijan province. This handicraft has both the simplicity of the rug (Kilim) style and the elegance and beauty of the carpet. The lack of sufficient information in this field has led to a close study of some of these motifs related to Verneh. Therefore, one of the most important objectives of the research is to introduce motifs, concepts and animal symbols hidden in Verneh, in order to expand knowledge about the artistic products of this region and examine the impact of nomadic life conditions on the nature of their products in these areas. The research method is applied in terms of nature and purpose and its findings were first done as field research. Then, the samples from the studies were matched with the general information and eventually examined. The results of this study show that the animal motifs created in verneh tell the truth about the material and social life of weavers and show a valuable collection in their life. Verneh’s paintings and motifs depict the nomadic way of life, the animal-dependent life in direct connection with nature, the adherence to the customs of the ancestors and the beliefs of these people. Animal motifs are a symbol of nomadic life, related to nomadic livestock.